(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Immunochemical methods of analysis, based on specific binding of the determined compound by appropriate antibodies, have widely entered into analytical practice and are used in various fields of medicine, agriculture, microbiological and food industries, and for environmental protection purposes. The indication of the formed antigen-antibody complex can be realised by introducing a label into one of the initial components of the reaction system, which can be easily detected by an appropriate highly sensitive physico-chemical method.